Laser Ablation of Abnormal Neurological Tissue Using Robotic NeuroBlate System (LAANTERN): 12-Month Outcomes and Quality of Life After Brain Tumor Ablation. (18th November 2021) - Kim, Albert H; Tatter, Steven; Rao, Ganesh; Prabhu, Sujit; Chen, Clark; Fecci, Peter; Chiang, Veronica; Smith, Kris; Williams, Brian J; Mohammadi, Alireza M; Judy, Kevin; Sloan, Andrew; et al.
Graphical Abstract: